North Korea: US and allied military options. Issue 9 (20th October 2016) - Unknown
Abstract : North Korean nuclear bomb and ballistic missile tests may require the United States and its regional allies to take a harder look at military options against North Korea. Pre-emptive or preventive attack is fraught with downsides. But uncertainties surrounding deterrence and worries about potential North Korean brinkmanship could keep that option salient.